Providers adherence to essential contents of antenatal care services increases birth weight in Bahir Dar City Administration, north West Ethiopia: a prospective follow up study - Tadese Ejigu Tafere; Mesganaw Fanthahun Afework; Alemayehu Woreku Yalew (BMC, 2018)
Abstract Background Low birth weight (LBW) is one of the most important factors affecting child morbidity and mortality worldwide. Antenatal care (ANC) is an opportunity for reaching pregnant women with a number of interventions that may be vital to their health and well-being of their infants. However, data on the link between ANC quality and LBW remain limited especially in developing countries. Therefore, this study was aimed at investigating the effect of ANC service quality on birth weight among pregnant women attending ANC at public health facilities of Bahir Dar City Administration, Bahir Dar, Ethiopia using provision of essential services by providers as proxy for quality of care. Methods Nine hundred seventy pregnant women with gestational age ≤ 16 weeks who came for their first ANC visit and selected by systematic sampling were enrolled and followed until delivery. Longitudinal data was collected during consultation with ANC providers using structured observation checklist. Women who gave birth at home and those who deliver a premature or still birth baby were excluded as data on birth weight could not be obtained for home deliveries and as the birth weight of the baby might be affected due to prematurity and still birth. Completed data were obtained from 718 women (since the rest women gave birth at home, we could not obtain birth weight data and we exclude them from analysis). The overall ANC service was considered as acceptable quality if women received ≥75th percentile of the essential ANC services. Generalized Estimating Equation was carried out to identify predictors of birth weight by controlling the cluster effect among women who received ANC services in the same facility. Results The prevalence of low birth weight (< 2500 g) was 7.8% (95%CI = 6.0%, 9.7%) with 1.4% versus 10.5% among those who received acceptable and not acceptable quality ANC services respectively, P-value< 0.001. Maternal nutritional advice, iron-folic acid supplementation, tetanus toxoid vaccination, maternal educational status, parity and age were determinants for birth weight. Conclusion and recommendation The study showed that access to quality ANC services led to good birth weight outcome. Strengthening adherence of providers to essential components of antenatal care through regular monitoring and need based capacity building is very important for reducing the risk of low birth weight.